2022
DOI: 10.1101/2022.05.24.493209
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“A CRISPR-dCas13 RNA-editing tool to study alternative splicing”

Abstract: Alternative splicing is an RNA processing used by the cell to increase its protein diversity and genome plasticity through generation of several transcripts from the same gene. It affects the vast majority of biological processes, from stem cell differentiation to cell metabolism. However, tools to properly study the role of a specific splice variant are still missing. With the discovery of the bacterial CRISPR system, a new era in nucleic acid editing has emerged. RNA-directed CRISPR/Cas13 RNAses were recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
(169 reference statements)
0
4
0
Order By: Relevance
“…Our analysis also suggests that longer gRNA spacers of 25-nt provided a much higher signal-to-noise ratio than shorter gRNA spacers of 22-nt, suggesting that longer spacers help stabilize the gRNA or form a more stable dCas13d/gRNA/target RNA ternary complex. The effect of spacer length on the efficacy of splicing modulation observed at a low MOI with more moderate gRNA expression appears to be clearer than the differences observed upon overexpression of both dCas13d and individual gRNAs 42,45,47,56 .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Our analysis also suggests that longer gRNA spacers of 25-nt provided a much higher signal-to-noise ratio than shorter gRNA spacers of 22-nt, suggesting that longer spacers help stabilize the gRNA or form a more stable dCas13d/gRNA/target RNA ternary complex. The effect of spacer length on the efficacy of splicing modulation observed at a low MOI with more moderate gRNA expression appears to be clearer than the differences observed upon overexpression of both dCas13d and individual gRNAs 42,45,47,56 .…”
Section: Discussionmentioning
confidence: 87%
“…Several studies indicated that gRNA length may affect the efficiency of Cas13d-mediated target RNA cleavage 42,45,47,56 . In our initial transfections, we used the 22-nt gRNA D [9,30] targeting the ISS-N1 region as a positive control segRNA.…”
Section: Specific Splicing Activation and Repression Through Transien...mentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian systems, Cas13 has been used for genome-wide knockdown screens, targeted RNA silencing, and nucleic acid detection (8,10,11). The use of catalytically inactive dCas13 fused to an effector domain has also enabled RNA editing and splicing applications (9,(12)(13)(14). In E. coli, the use of dCas13 for translational repression (CRISPRi) and activation (CRISPRa) of endogenous transcripts has been demonstrated recently (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%